The Use and Value Sources of Information Used By Women During Pregnancy : Scoping Review - Selvia, Anisya; Ernawati, Dwi (International Journal of Scientific Research and Management (IJSRM), 2019)
Pregnant women, especially in the age of technologically sophistication as today have a great opportunity to find information sources about pregnancy by using various media. They can get this information through websites, blogs, online discussion forums, applications and social media platforms. Pregnant women not only use information sources to obtain information but also can share information with other users on social media.The aim of scoping review is to know the use and value sources of information used by women during pregnancy. This study employed Sciendirect and pubmed to find relevant articles, using search terms “Digital Media”, “ Information”, “seeking” and “pregnancy”. The Publication dates of those articles ranged from 2012 to 2018. 1171 was found and sorted based on inclusion and exclusion criteria, resulting in eleven articles that had been used in this study. Thematic analysis was used to identify key consepts. We grouped these key consepts into four emergent themes : use and value of Mobile Health, use and value of the Internet, health information search and the impact of social media as information search media in pregnancy.